A Pyrus communis gene for p-hydroxystyrene biosynthesis, has a role in defense against the pear psylla Cacopsylla biden. (May 2019) - Yahyaa, Mosaab; Rachmany, Dor; Shaltiel-Harpaz, Liora; Nawade, Bhagwat; Sadeh, Asaf; Ibdah, Muhammad; Gerchman, Yoram; Holland, Doron; Ibdah, Mwafaq
Abstract: Styrene analogs are known to be naturally synthesized in the leaves of pears and in other plant species, including several trees in the Styracaceae family. Styrene analogs are potential contributors to the aroma of wine, perfumes, pharmaceuticals, and other fermented foods and beverages. In addition, styrene analogs perform important ecological functions such as insecticidal and antifeedant activities against insects. We showed here that exogenous applications of styrene and p -hydroxystyrene caused a dramatic reduction the number of eggs laid by psylla and of subsequent nymph survival. Despite their importance specific reactions that lead to the biosynthesis of the styrene analogs in pear are unknown. To identify genes involved in the synthesis of these metabolites, existing genome databases of the Rosaceae were screened for pear genes with significant sequence similarity to bacterial phenolic acid decarboxylase. Herein described are the isolation and characterization of a pear phenolic acid decarboxylase, designated PyPAD1, which catalyzed the decarboxylation of p -coumaric acid and ferulic acid to p -hydroxystyrene and 3-methoxy-4-hydroxystyrene respectively. Its apparent Km values for p -coumaric acid and ferulic acid were 34.42 and 84.64 μM, respectively. The PyPAD1 preferred p -coumaric acid to ferulic acid as a substrate by a factor of 2.4 when comparing catalytic efficiencies in vitro . Expression analysis of PyPAD1 showed that the gene was transcribed in all five pear genotypes examined. However, transcript abundance was increased in correlation with the presence of p -hydroxystyrene in resistant cultivars Py-701 and Py-760 and in the sensitive cultivar Spadona when grafted on these resistant cultivars. Thus, PyPAD1 appears to be responsible for the decarboxylation of the p -coumaric acid, and for the production of metabolites that are active against pear psylla. Graphical abstract: Image 1 Highlights: Phenolic acid decarboxylase was identified and characterized from pear leaves. PyPAD1 catalyses the decarboxylation of p -coumaric acid and ferulic acid to p -hydroxystyrene and 3-methoxy-4-hydroxystyrene. PyPAD1 prefers p -coumaric acid over ferulic acid as a substrate. Expression analysis suggests that the enzyme may play a crucial role in biosynthesis of styrene analogs.